Patterns of body mass change during moult in three different goose populations - Fox, Anthony D; Kahlert, Johnny; Walsh, Alyn J; Stroud, David A; Mitchell, Carl; Kristiansen, Jens N; Hansen, Ebbe Bøgebjerg (Wildfowl, 1998)
We used measurement of wing feather length as an index of moult stage to assess body mass changes amongst samples of geese caught from three different wild populations during the period of regrowth of flight feathers. Amongst male and female Greenland White-fronted and Canada Geese captured in west Greenland, there were no significant correlations between body mass and wing length. This pattern fits the generally accepted theory that moulting geese do not suffer nutritional stress during the regrowth of remiges (ie that nutritional and energetic needs of the geese during moult can be met from exogenous sources). In contrast, average body mass of Greylag Geese on the Danish island of Saltholm fell by between 12 and 26% during moult, confirmed by field observations of consistent reductions in abdominal profile scores (a field assessment of the extent of abdominal fat stores). It would appear from these data that moulting Greylags on Saltholm do utilise body stores accumulated prior to the flightless period to sustain birds through the moult period, and the significance of these findings are discussed in the light of existing information.